Remineralization Effects of Anticariogenic Products on Demineralized Enamel: an in Vitro Study. - Han, Jekyung; Shin, Seungwoo; Shin, Jisun; Kim, Jongsoo; Shim, Younsoo; An, Soyoun; Kim, Jongbing (International Journal of Engineering and Technology, 2018)
Background/Objectives: The aim of this study was to compare the remineralization effects of two types of anticariogenic products on artificially demineralized enamel.Methods/Statistical analysis: Extracted 60 premolars were decalcificatied in artificial acidic solution at 37℃ for 7 days. Two anticariogenic products, Clinpro™ Tooth Cream (CTC) and Tooth Mousse-Plus® (TMP), were applied on demineralized surface for 3weeks.The changes of surface microhardness values of each group were measured with Vickers surface hardness tester.Findings:Microhardness values of CTC and TMP were increased during 3weeks. Mean values ofmicrohardness values of CTC was higher than TMP.Mean values ofmicrohardness values was increased in 1st week <2nd week <3rd week(p < 0.05). There was a difference of significance between each week groups.Microhardness values of CTC was increased rapidly in 1st week. Then slower than 1st week during 2nd and 3rd weeks. TMP was increased slowly in 1st week then, faster in 2nd week.CTC was most effective during the initial week, and it was noted that a TMP could be expected to work if it was applied for at least two weeks.Improvements/Applications:This has shown that If CTC and TMP are used for more than two weeks, it is valid for remineralization of the initial demineralized lesion.